Determinants of ASEAN Banking System Stability: Panel Regression Analysis of Z-Score and NPL - Laras Cahya Fatmawati; Mohamad Adam; Muizzuddin (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2025)
This research examines the determinants of banking stability in six ASEAN countries (2019–2023) using a microprudential framework. Analyzing 438 commercial banks through Fixed Effect Models, we measure stability using the Z-Score (insolvency risk) and the NPL ratio (credit risk). The results identify ROA as the most influential determinant positively affecting the Z-Score while reducing NPL thereby confirming profitability’s crucial role in strengthening banking stability. Moreover, bank size negatively affects both stability measures, suggesting that larger institutions may face systemic vulnerabilities despite their risk-absorption capacity. In addition, inflation increases the Z-Score, while GDP growth reduces NPL. CAR has a negative and significant effect on the Z-Score but is not significant for NPL, while LDR and BOPO do not show significant effects in either model. These findings emphasize that profitability management and strategic scaling are pivotal for enhancing financial resilience in ASEAN’s banking sector.